Epidemiology and therapeutic efficacy of a synthetic pyrethroid against Haematopinus tuberculatus (Phthiraptera: Haematopinidae) in Bubalus bubalis - Sajid, Muhammad Sohail; Iqbal, Asif; Rizwan, Hafiz Muhammad; Naz, Saima; Maqbool, Mahvish; Malik, Muhammad Abdullah; Jawad-ul-Hassan, Muhammad (Journal of the Hellenic Veterinary Medical Society, 2022)
Lice (Insecta: Pthiraptera) are common ectoparasite of buffalos (Bubalis bubalis) causing huge economic loss. An epidemiological survey was conducted in selected tehsils (administrative division) of Faisalabad district to determine the prevalence of lice infestation and the efficacy of cypermethrin (CYP) against lice infestation in buffalos. To determine the efficacy of CYP, 40 lice-infested buffaloes were divided into two groups i.e. drug-treated group and control group (each group contains 20 animals). Cypermethrin drug was used as pour-on at day 0 and lice counts were conducted on days 0, 7, 21, 35, 49, and 63 from predilection sites of each animal. Only one species of sucking louse Haematopinus tuberculatus was found in buffalo population of Faisalabad district. The overall prevalence of lice infestation was 37.76%. The variable like age and sex showed significant (P<0.05) variation of lice infestation while breed showed insignificant variation. Among extrinsic factors, seasons, floor pattern, and feeding system showed significant association (P<0.05) with lice infestation, while animal keeping as free or tethered and tehsils showed an insignificant association. On day 7, 100% effective results were obtained while 99.6% at day 21 and 100% from day 35 till day 63. No clinical adverse reaction was observed during this trial and cypermethrin was found efficacious. Based on these results it can be concluded that cypermethrin is an effective drug against lice infestation.